2016
DOI: 10.1093/mnras/stw867
|View full text |Cite
|
Sign up to set email alerts
|

Spectropolarimetric capabilities of Ca ii 8542 Å line

Abstract: The next generation of space and ground-based solar missions aim to study the magnetic properties of the solar chromosphere using the infrared Ca ii lines and the He i 10830Å line. The former seem to be the best candidates to study the stratification of magnetic fields in the solar chromosphere and their relation to the other thermodynamical properties underlying the chromospheric plasma. The purpose of this work is to provide a detailed analysis of the diagnostic capabilities of the Ca ii 8542Å line, anticipa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 44 publications
2
58
0
Order By: Relevance
“…The Ca II infrared (IR) triplet lines are well suited for flare diagnostics due to their good sensitivity to physical parameters, including magnetic field, in the solar photosphere and chromosphere (Pietarila et al 2007;Cauzzi et al 2008;de la Cruz Rodríguez et al 2012;Quintero Noda et al 2016). Furthermore, calcium is singly ionized under typical chromospheric conditions, with negligible nonequilibrium and partial redistribution effects for the Ca II IR lines (Uitenbroek 1989;Wedemeyer-Böhm & Carlsson 2011), making their modeling and interpretation of the observations more straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…The Ca II infrared (IR) triplet lines are well suited for flare diagnostics due to their good sensitivity to physical parameters, including magnetic field, in the solar photosphere and chromosphere (Pietarila et al 2007;Cauzzi et al 2008;de la Cruz Rodríguez et al 2012;Quintero Noda et al 2016). Furthermore, calcium is singly ionized under typical chromospheric conditions, with negligible nonequilibrium and partial redistribution effects for the Ca II IR lines (Uitenbroek 1989;Wedemeyer-Böhm & Carlsson 2011), making their modeling and interpretation of the observations more straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hinode/SP was strongly supported by ASP (Elmore et al 1992) observations and SDO/HMI benefited from groundbased observations but also from specific supporting works as Norton et al (2006). We performed a similar study in Quintero Noda et al (2016) aiming to support future misc 2016 The Authors sions with chromospheric polarimetry as the main target, for instance, Solar-C (Katsukawa & Solar-C Working Groups 2011;Katsukawa et al 2012;Watanabe 2014;Suematsu & Solar-C Working Group 2016). We concluded that the Ca ii 8542Å is a unique spectral line that is sensitive to a large range of heights, from the photosphere to the chromosphere (see Figure 4 and 6 of the mentioned work).…”
Section: Introductionmentioning
confidence: 72%
“…We have selected a small fragment of the simulated snapshot, see Figure 5. This fragment is different than the one used in Quintero Noda et al (2016), i.e. it is three times larger and contains most of the magnetic patch located on the right side of the original field of view (see Figure 2 of Carlsson et al (2016)).…”
Section: Synthesis Of Stokes Profiles Using a Realistic 3d Modelmentioning
confidence: 98%
“…Additionally, and according to Quintero Noda et al (2016), these wing signals do still have a strong chromospheric contribution, with the response functions peaking very high in the atmosphere.…”
Section: Polarimetric Datamentioning
confidence: 87%